Survey of the Human Pancreatic β-Cell G1/S Proteome Reveals a Potential Therapeutic Role for Cdk-6 and Cyclin D(1) in Enhancing Human β-Cell Replication and Function In Vivo - Fiaschi-Taesch, Nathalie (American Diabetes Association, 2009)
OBJECTIVES: To comprehensively inventory the proteins that control the G1/S cell cycle checkpoint in the human islet and compare them with those in the murine islet, to determine whether these might therapeutically enhance human β-cell replication, to determine whether human β-cell replication can be demonstrated in an in vivo model, and to enhance human β-cell function in vivo. RESEARCH DESIGN AND METHODS: Thirty-four G1/S regulatory proteins were examined in human islets. Effects of adenoviruses expressing cdk-6, cdk-4, and cyclin D(1) on proliferation in human β-cells were studied in both invitro and in vivo models. RESULTS: Multiple differences between murine and human islets occur, most strikingly the presence of cdk-6 in human β-cells versus its low abundance in the murine islet. Cdk-6 and cyclin D(1) in vitro led to marked activation of retinoblastoma protein phosphorylation and cell cycle progression with no induction of cell death. Human islets transduced with cdk-6 and cyclin D(1) were transplanted into diabetic NOD-SCID mice and markedly outperformed native human islets in vivo, maintaining glucose control for the entire 6 weeks of the study. CONCLUSIONS: The human G1/S proteome is described for the first time. Human islets are unlike their rodent counterparts in that they contain easily measurable cdk-6. Cdk-6 overexpression, alone or in combination with cyclin D(1), strikingly stimulates human β-cell replication, both in vitro as well as in vivo, without inducing cell death or loss of function. Using this model, human β-cell replication can be induced and studied in vivo.